Effect of different packaging conditions and temperatures on physicochemical and microbiological quality of Tualang honey-marinated chicken meat - Yousof, K.; Nur Hanani, Z. A.; Kumar, P.; Ismail Fitry, M. R.; Nor Khaizura, M. A. R. (ACS Publisher, 2024)
The present study evaluated the microbial quality, pH, and water activity of Tualang honey (TH) marinated chicken breast meat under various temperatures and packaging conditions. Chicken breast meat samples were marinated in marinades containing 50% TH for 24 h at 4 ºC. The samples were drained and packaged under aerobic and vacuum packaging conditions and stored at 5, 10, and 25 ºC for 7, 4, and 2 days, respectively. The highest increase in TPC was noted in samples stored at 25 ºC and the lowest in samples stored at 5 ºC. At 10oC until 12 h storage, the total plate count was 4.84 log CFU/g, and for 5 ºC at 72 h, the total plate count was 5.82 log CFU/g. The pH value at 25 ºC differed significantly (p<0.05) among the control, honey-marinated chicken with normal packaging (HCNP), and honey-marinated chicken with vacuum packaging (HCVP) samples. Control samples had the highest pH and water activity as compared to other samples at all temperatures studied. Thus, marinating chicken breast meat with 50% Tualang honey marinades improved the microbial quality, and this effect was better observed at low temperatures and under vacuum packaging.